Surgery for infective endocarditis - Essop, M.R. (SA Heart Journal, 2017)
The last decade has seen many changes in the landscape of infective endocarditis (IE) – ranging from the epidemiology, microbiology, diagnostic techniques and indication for antibiotic prophylaxis. Unfortunately, the role of surgery in the patient with endocarditis, including the indication, timing and type of surgery continues to be plagued by controversy. Although surgery has an important and established role in critically ill patients with endocarditis, the choice between medical therapy and surgery is often less clear cut and poses a major challenge to the physician treating this condition. The following article summarises some of these controversies including indications for surgery in native and prosthetic valve endocarditis, the timing of surgery, the choice of prostheses and issues surrounding anti-coagulation.